Organizational Change and Organizational Effectiveness of Secondary Banking System in Albania - Shoraj, Dritan; Zogjani, Adem; Govori, Fadil (International Journal of Management Excellence (ISSN: 2292-1648), 2014)
Continuous organizational changes are required as well as successful implementation approaches of modern managerial methods. However, organizational changes in Business Organizations may often occur at inconvenient time, subject to the psychological preparation of employees or the whole staff in general. In these circumstances, the employees displayed strong resistance to accept changes although they may be decisive for the survival of Business Organizations. Further, what makes the Business Organization employees accept or refuse organizational changes? Which is the impact of their resistance on change implementation? Is it closely connected with their personal interests or is it merely a contradiction for the purpose of convenience? These questions and many others will be answered during this investigation through an empirical and theoretical analysis. The study will show the connection between organizational changes in terms of organizational effectiveness. Additionally, it will present a clear overview of the reality of Albanian Business Organizations regarding the organizational change and their mode of operation